The role of leadership styles in shaping work engagement: Mapping multi-sectoral trends through bibliometric and systematic review - Iqbal Saffariz Santosa; Erwan Agus Purwanto; Sumaryono Sumaryono; Puguh Prasetya Utomo (Social Sciences and Humanities Open)
This study investigates the relationship between leadership styles and work engagement through an integrated bibliometric analysis and systematic review of 108 Scopus-indexed articles published between 2009 and 2024, with a focused analysis of 48 eligible studies. While transformational, servant, and inclusive leadership styles consistently correlate with higher engagement, the review exposes several conceptual and geographical gaps. Emerging paradigms such as digital, green, and transglobal leadership remain underexamined, and Southeast Asian contributions are notably scarce. Furthermore, the fragmented use of mediators and moderators, often without theoretical integration, limits the explanatory power of current models. This review calls for a shift from static typologies and instrumental engagement views toward relational, ethically conscious, and context-sensitive leadership frameworks. It emphasizes the importance of incorporating institutional norms, cultural logics, and power dynamics into future research. By advancing theoretical synthesis through models such as the Job Demands-Resources framework, Social Exchange Theory, and Institutional Theory, the study contributes to a more inclusive and critically informed understanding of leadership in contemporary organizational contexts.